2011
DOI: 10.1029/2010jc006819
|View full text |Cite
|
Sign up to set email alerts
|

Wave runup during extreme storm conditions

Abstract: [1] Video measurements of wave runup were collected during extreme storm conditions characterized by energetic long swells (peak period of 16.4 s and offshore height up to 6.4 m) impinging on steep foreshore beach slopes (0.05-0.08). These conditions induced highly dissipative and saturated conditions over the low-sloping surf zone while the swash zone was associated with moderately reflective conditions (Iribarren parameters up to 0.87). Our data support previous observations on highly dissipative beaches sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
153
3
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(182 citation statements)
references
References 43 publications
20
153
3
6
Order By: Relevance
“…6). Consistent with these findings, swash time series measured during the same storm were dominated by energy at infragravity frequencies (Senechal et al, 2011b). Surveys performed near the onset and after the peak of S3 confirm the limited effect of this storm on beach erosion with beach three-dimensionality only increasing slightly.…”
Section: Hydro-and Morphodynamic Changessupporting
confidence: 69%
“…6). Consistent with these findings, swash time series measured during the same storm were dominated by energy at infragravity frequencies (Senechal et al, 2011b). Surveys performed near the onset and after the peak of S3 confirm the limited effect of this storm on beach erosion with beach three-dimensionality only increasing slightly.…”
Section: Hydro-and Morphodynamic Changessupporting
confidence: 69%
“…This variability is probably in large part due to the variability in exposure of the beaches involved to the deep water wave conditions. In contrast to the dependency of short-wave swash on beach face gradient, both Stockdon et al, (2006) and Senechal et al (2011) found no relationship between the infragravity swash height and beach face gradient. On the other hand Ruggiero et al (2004) found that the significant infragravity swash height was inversely related to beach gradient.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…Holman and Sallenger, 1985;Ruessink et al, 1998 Figure 10 in Ruessink et al, 1998or in Senechal et al, 2011. This variability is probably in large part due to the variability in exposure of the beaches involved to the deep water wave conditions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…These errors could therefore be overcome by elevating the cameras, as in previous works (e.g., McCarrol et al [70] (55 m), Bracs et al [65] (44 m), Sénéchal et al [32], Almar et al [38] (27 m), Vousdoukas et al [47] (20 m), Abessolo Ondoa et al [69] (15 m)). …”
Section: Comparing Video-to Lidar-based Topographymentioning
confidence: 90%